Behavior of Third Phase of Mixed Solution Containing Hydroxyphosphate in PUREX Process - Ying-jie LUO; Rui-cai WU; Gang CHEN; Shuang-ling TANG (He huaxue yu fangshe huaxue)
During spent fuel reprocessing, TBP may form hydroxyl-containing phosphate ester under radiation and high temperature conditions. The phosphate ester with hydroxyl group is a substance with hydrophilic and lipophilic groups, which is prone to form a third phase between the aqueous phase and the oil phase when mixed and contacted with 30%TBP-kerosene, HNO3, HDBP and zirconium(Zr4+). Moreover, part of the oil and water phases will also be encapsulated in the third phase, so that the generation of the third phase is greatly increased. The generation of the third phase will cause density effect and volume effect, reduce the decontamination efficiency of the extractant, and even cause liquid flooding, inverted phase and other abnormalities during the operation of the equipment, thus affecting the normal operation of the process. In this paper, the hydroxyl-containing phosphate ester was synthesized and the generation of the third phase in the mixed solution of Zr/HDBP-30%TBP-kerosene/HNO3/hydroxyl-containing phosphate ester was studied, to investigate the effects of zirconium concentration, HDBP concentration and mass concentration of hydroxyl-containing phosphate ester on the third phase. The results show that the generation of the third phase is positively correlated with the zirconium concentration in the range of 0-3×10−2 mol/L, the generation of the third phase is firstly increased and then decreased in the range of 0-25 g/L for HDBP, and the generation of the third phase is firstly increased rapidly and then basically remained unchanged in the range of 0-60 g/L for the mass concentration of hydroxyl-containing phosphate ester. The basic structure of the third phase is analyzed by using X-ray diffractometer and infrared spectroscopy, and the results show that the third phase is an amorphous state amorphous body, and the structure is mainly of Zr-DBP type.